2014
DOI: 10.7314/apjcp.2014.15.15.6103
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Beta-Catenin Expression in Patients with Esophageal Carcinoma: a Meta-analysis

Abstract: Many studies have reported β-catenin involvement in the development of esophageal carcinoma (EC), but its prognostic significance for EC patients remains controversial. Therefore, we conducted this meta-analysis to explore the issue in detail. After searching PubMed, EMBASE, Web of Science, and Chinese Biomedical Literature Database, we included a total of ten relevant studies. We pooled the overall survival (OS) data using RevMan 5.2 software. The results showed that aberrant expression of β-catenin was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
4
1
Order By: Relevance
“…While our results suggested that CDH1 or CTNNB1 expression alone did not affect the prognosis of patients, whether CDH1 and CTNNB1 expression may serve as a good prognostic marker in esophageal cancer is still controversial. In the meta-analysis, there are two reports that CDH1 expression alone is a valid prognostic marker [36] and aberrant CTNNB1 alone is a prognostic factor [37]. Our data suggested that CDH alone or CTNNB1 alone did not affect the prognosis of the patients with esophageal cancer, though we could not clarify the discrepancy between their data and ours.…”
Section: Discussioncontrasting
confidence: 89%
“…While our results suggested that CDH1 or CTNNB1 expression alone did not affect the prognosis of patients, whether CDH1 and CTNNB1 expression may serve as a good prognostic marker in esophageal cancer is still controversial. In the meta-analysis, there are two reports that CDH1 expression alone is a valid prognostic marker [36] and aberrant CTNNB1 alone is a prognostic factor [37]. Our data suggested that CDH alone or CTNNB1 alone did not affect the prognosis of the patients with esophageal cancer, though we could not clarify the discrepancy between their data and ours.…”
Section: Discussioncontrasting
confidence: 89%
“…Li et al (9) revealed that aberrant expression of β-catenin, which was defined as "reduced expression in membrane" or "overexpression in cytoplasm/ nucleus", significantly influenced the survival of patients with gastric cancer (HR: 1.85; 95% CI: 1.39-2.46). Zeng et al (52) also suggested that altered expression of β-catenin could serve as a predicative factor of poor prognosis for patients with esophageal carcinoma. Zhang et al (50) and Chen et al (53) have demonstrated that positive β-catenin expression in cytoplasm/nucleus was significantly associated with poor prognosis of breast cancer and hepatocellular carcinoma respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous meta-analyses have proven that nuclear β-catenin overexpression predicts progressive disease and unfavorable survival in colorectal cancer [25], lung cancer [26, 27], hepatocellular cancer [28], breast cancer [29], esophageal cancer [30], and gastric cancer [31]. As the prognostic value of β-catenin in pancreatic cancer remains controversial, a meta-analysis was needed to explore the issue clearly.…”
Section: Discussionmentioning
confidence: 99%